Molecular Docking studies of Benzodiazepine Derivatives With GABA(B) Receptor - Satish Kumar Sarankar; Sushma Somkuwar (International Journal of Toxins and Toxics, 2024)
Benzodiazepines (BZDs) are pharmacologically significant compounds that act by binding to GABA A neurotransmitter receptors, subsequently augmenting GABA-induced chloride ion flux, consequently inducing neuronal hyperpolarization. Benzodiazepines are commonly used in the treatment of sleep disorders, anxiety, muscle spasms, seizure disorders, and some forms of depression. The primary inhibitory neurotransmitter, GABA, functions on two types of receptors: the ligand-gated GABA A/C receptors and the G protein-coupled GABA B receptors. These neurotransmitters play crucial roles in modulating numerous synapses, influencing both pre- and post-synaptic activity, and remain noteworthy targets for the treatment of various brain disorders, including addiction.Since both the GABA A and GABA B are subunits of the same receptor, binding affinity of BZDs to GABA B receptor have been assessed using docking approach in present work. Some of the most commonly used BZDs were preferred for docking and studies showed that they have got the affinity to bind with GABA B receptor too. This study opens a new path for repurposing BZDs for variety of pharmacological actions as well as for researchers to work in this new direction.
Keywords: Anxiety; Benzodiazepines; Docking; GABA A & B